(untitled) (Journal of Nepal Geological Society, 2018)
The Central Research Institute of Electric Power Industry conducted research to develop a long-term monitoring technology to clarify pore water pressure and water chemistry in drilled boreholes. An automatic data acquisition system for the long-term monitoring was also developed. The automatic data acquisition system has an independent electric power supply and data communication system. The electric power is supplied from solar and wind power. The data communication is secured through a satellite or 3G/4G line. A very low power consumption system can be readily installed by creating personal area networks between measuring devices using Zigbee digital radio. A demonstration of the system was conducted under harsh natural conditions for 18 months. It was confirmed that the system has sufficient reliability for actual operation.